Fake News in Social Network: A Comprehensive Review - Omar, Mohamed Rasheed; Abdulazeez, Adnan (AI Society & STMIK Indonesia, 2024)
Fake news has become a significant challenge in the digital age, evolving from its historical roots in traditional media to becoming a pervasive issue on social media platforms. This paper presents a comprehensive review of the scope and mechanisms of fake news propagation in the digital era, focusing specifically on social media. It examines the historical development of fake news and assesses the effectiveness of current detection methods. Various aspects of fake news, including its spread and the associated challenges, are explored through a detailed methodological approach that integrates both technological and sociological strategies. The goal is to enhance the accuracy of detection methods and mitigate the impact of fake news. This review aims to synthesize existing paper, identify gaps in the current knowledge, and recommend directions for future paper, ultimately seeking to protect public discourse and maintain the integrity of information in the digital landscape.